Al calor de un disenso - Berckemeyer Olaechea, Fernando (2020)
Dissent in arbitration is often not well-regarded. It is argued that dissenting votes debilitate the authority of the awards and thus that of arbitration since they only promote the career, or vent the ego, of the arbitrator who did not convince the majority. In this paper, the author, contrary to the prevailing opinion, defends the convenience of the dissenting vote as an element which –even when it remains as a slight possibility– serves to the proper functioning of the tribunal as a “mind-of-three”.Consequently, the paper relativizes the data generally used to argue against dissent in arbitration, assesses the different types of dissenting votes and challenges the standards by which the current state of thinking holds this mechanism should be limited and monitored. Instead, the author proposes a system in which “each dissenting vote is the best judge of itself” and where there are only ex post and market dissent controls.